Unlocking Agile's Missed Potential - Webber, Robert (John Wiley & Sons, Incorporated, 2022)
UNLOCKING AGILE'S MISSED POTENTIAL Agile has not delivered on its promises. The business side expected faster time to market, but they still experience the long delays of bloated releases. Engineers thought they would be given time to build the product right the first time, but they are rushed under pressure to deliver new features within impossible schedules. What went wrong? The culprit is feature-based waterfall release planning perpetuated in a vain attempt to achieve business predictability. Agile didn't address the business need for multi-year financial predictability. The Agile community's answer was the naïve response, "The business needs to be more Agile." Waterfall release planning with fixed schedules undercuts a basic tenet of Agile development - the need to adjust content delivered within a timebox to account for evolving requirements and incorporation of feedback. Agile without flexible content is not Agile.
Keywords: Agile software development; Méthodes agiles (Développement de logiciels)